Cadmium and iron decorated ZnO nanoparticles: Effects on physical, electrochemical and antibacterial performance. Issue 4 (March 2020) - D, Neena; Humayun, Muhammad; Lu, Dingze; Mohan, Velram Balaji; Fu, DeJun; Gao, Wei
Abstract: Herein, powder samples of Cd/Fe co-doped ZnO nanoparticles have been synthesized via sol-gel route. The impact of co-doping on physical properties of the samples is examined by various techniques. The XRD patterns show that the samples possess hexagonal wurtzite structure of the parent ZnO. In photoluminescence spectra, red and blue shifts observed for near-band-edge UV emission and green-band (GB) emission, respectively, confirming substitutional incorporation of Cd/Fe into the ZnO lattice. The Cd/Fe co-doped ZnO gives superior electrochemical activities because of high charge collection and facilitate the electrons at the interfaces of doped ZnO and the electrode layer. Mössbauer studies reveal that disorders enhance close to Fe 3+ as Cd/Fe co-doping increases. C3F3 sample shows higher ΔD1 compared to the other samples, suggesting that more Fe 3+ exist close to the defective sites. The disk diffusion method was used for antibacterial performance of two bacteria Pseudomonas aeruginosa ( P. aeruginosa ) and Ba cillus flexus ( B.flexus ) . C2F2 shows the highest antibacterial activates among all samples.